Reframing remission in severe asthma : a conceptual framework for distinguishing disease activity versus damage - Porsbjerg, Celeste; Rupani, Hitasha; Brannan, John D.; Ueki, Shigeharu; Nawijn, Martijn C.; Erjefält, Jonas S.; Chanez, Pascal; Anderson, Gary P.; Pavord, Ian D. (The Lancet Respiratory Medicine, 2025)
Remission is emerging as a feasible treatment goal in moderate-to-severe asthma, driven by the success of biologic therapies in controlling inflammation and reducing exacerbations. Yet current definitions of remission—focused on symptom control, lung function, and corticosteroid reduction—lack precision, can only be ascertained retrospectively, and do not reflect the underlying mechanisms and pathology that drive disease progression. This gap limits the clinical applicability of these definitions and might obscure opportunities for early, disease-modifying intervention. In this Series paper, we propose a refined framework for understanding and reaching remission, centred on distinguishing modifiable disease activity from irreversible remodelling and comorbidity-related factors that contribute to disease burden. We introduce the concept of at-risk asthma as a crucial phase characterised by high disease activity and immune dysregulation, in which timely intervention might prevent irreversible airway and extrapulmonary damage and support long-term disease modification. We examine how symptoms, lung function impairment, and exacerbations can arise from distinct and overlapping mechanisms, underscoring the need for careful attribution in clinical assessment. We also outline four key pathophysiological domains—airway hyper-responsiveness, immune hyper-responsiveness, immune remodelling, and structural remodelling—and describe their temporal evolution and implications for treatment responsiveness. Finally, we present a domain-based strategy for assessment and intervention, linking targeted therapies to underlying mechanisms. This approach supports more personalised treatment decisions and redefines remission, not simply as the absence of symptoms, but as stabilisation of disease biology. As the field advances towards earlier intervention and more tailored application of biologics in at-risk asthma, such a framework could be essential to improve long-term outcomes and prevent overtreatment of irreversible disease.
Publisher Copyright: © 2025 Elsevier Ltd